ChemInform Abstract: Pd‐Catalyzed Intramolecular Regioselective Arylation of 2‐Pyrones, Pyridones, Coumarins and Quinolones by C—H Bond Functionalization. Issue 10 (March 2015) - Nolan, Marie‐Therese; Bray, Joshua T. W.; Eccles, Kevin; Cheung, Man Sing; Lin, Zhenyang; Lawrence, Simon E.; Whitwood, Adrian C.; Fairlamb, Ian J. S.; McGlacken, Gerard P.
Abstract The regioselective Pd‐catalyzed cyclization of a number of heterocyclic substrates without added phosphine ligands is reported.